EGFR transcription in non‐small‐cell lung cancer tumours can be revealed in ctDNA by cell‐free chromatin immunoprecipitation (cfChIP). Issue 11 (18th September 2021) - Månsson, Christoffer Trier; Vad‐Nielsen, Johan; Meldgaard, Peter; Nielsen, Anders Lade; Sorensen, Boe Sandahl
Abstract : Determination of tumour‐specific transcription based on liquid biopsies possesses a large diagnostic and prognostic potential in non‐small cell lung cancer (NSCLC). Cell‐free DNA (cfDNA) packed in nucleosomes mirrors the histone modification profiles present in the cells of origin. H3 lysine 36 trimethylation (H3K36me3)‐modified nucleosomes are associated with active genes, and therefore, cell‐free chromatin immunoprecipitation (cfChIP) of H3K36me3‐associated cfDNA has the potential to delineate whether transcription of a particular gene is occurring in the cells from which its cfDNA originates. We hypothesized that cfChIP can delineate transcriptional status of genes harbouring somatic cancer mutations and analysed the recurrently observed EGFR‐L858R mutation as an example. In representative NSCLC cell lines, the relationship between wild‐type (WT) and mutated EGFR transcriptional activity and mRNA expression levels was analysed using H3K36me3 ChIP and EGFR mRNA reverse transcription quantitative PCR (RT‐qPCR), respectively. The ChIP analysis showed that both WT and mutated EGFR are transcribed and that mRNA is similarly expressed per EGFR copy. Based on this observation, we proceeded with EGFR cfChIP using blood plasma from NSCLC patients harbouring the EGFR‐L858R mutation. EGFR‐WT fragments can originate from both nontumour cells with no or low EGFR transcription and tumour cells with active EGFR transcription, whereas EGFR‐L858R fragments must specifically originate from tumour cells. H3K36me3 cfChIP followed by droplet digital PCR (ddPCR) revealed significantly higher enrichment of EGFR‐L858R compared to EGFR‐WT fragments. This is in alignment with EGFR‐L858R being actively transcribed in the NSCLC tumour cells. This study is proof‐of‐principle that cfChIP can be used to identify tumour‐specific transcriptional activity of mutated alleles, which can expand the utility of liquid biopsy‐based cfDNA analyses to enhance tumour diagnostics and therapeutics. Abstract : Cell‐free chromatin immunoprecipitation (cfChIP) is a novel technique that can be used to investigate tumour gene expression in liquid biopsies. Up to our knowledge, this is the first study evaluating tumour gene activity based on cfChIP enriched mutated alleles. Here, we focussed on the recurrently observed EGFR‐L858R mutation in non‐small cell lung cancer and observed EGFR‐L858R displayed higher cfChIP enrichment than EGFR‐WT. Our research demonstrates that cfChIP has the potential to expand the utility of liquid biopsies in cancer.